Penerapan Azas Kekeluargaan dan Keadilan pada Penyelesaian Kredit Bermasalah pada Pembiyaan Perumahan Di Indonesia - Rosyidi Hamzah (COSTING : Journal of Economic, Business and Accounting, 2020)
The house is a basic need for everyone. To assess the suitability of life of a community one indicator is the house. With a credit system for purchasing a house, most Indonesians can own a house. When the community was unable to pay home loan installments, the house will be scribbled by banks like this house in a bank escort. By drafting the debtor's house for not being able to pay housing loans, provides social and psychological sanctions to the debtor. Losses due to social and psychological sanctions for the debtor are more severe compared to sanctions that are material. This practice is not in accordance with the principle of kinship and the principle of justice which is an inseparable part of the Pancasila economic system. Keyword : Housing finance, family and justice principle